Effect of Antimelanotic Treatment and Vacuum Packaging on Melanosis and Quality Condition of Ice Stored Farmed Tiger Shrimp (Penaeus monodon) - Reddy, Vijay Kumar; Shinde, Pradnya A; Sofi, Faisal R; Shelar, Piyusha S; Patange, SB (SAARC Journal of Agriculture, 2014)
The objective of the study was to evaluate the effect of vacuum packaging in combination with antimelanotic treatment on quality characteristics and melanosis in farmed tiger shrimp (Penaeus monodon) collected from Ratnagiri region of Maharashtra. The processed shrimps were treated with sulfite mixture in water (30 g kg-1) and divided into two lots each with 250 shrimps. One of them was vacuum packed, the other was air packed and stored under ice. The ice stored shrimps were analyzed for quality attributes and melanosis for a period of 27 days. The treated vacuum packed shrimps had a shelf life of 24 days, whereas air packed shrimp had 16 days only. Melanosis was absent in the shrimps from both the lots throughout the storage period. Based on the results, it could be concluded that the combination of antimelanotic treatment (sulphite mixture) and packaging could significantly delay the occurrence of melanosis and increase the storage life of shrimp in ice. DOI: http://dx.doi.org/10.3329/sja.v11i2.18400 SAARC J. Agri., 11(2): 33-47 (2013)